2021
DOI: 10.3389/fimmu.2021.737601
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Extract Rich in Triterpenic Acid and Polyphenols from Olea europaea Promotes Systemic Immunity and Protects Atlantic Salmon Smolts Against Furunculosis

Abstract: In the present study, the modulation of the transcriptional immune response (microarray analysis) in the head kidney (HK) of the anadromous fish Atlantic salmon (Salmo salar) fed a diet supplemented with an olive fruit extract (AQUOLIVE®) was evaluated. At the end of the trial (133 days), in order to investigate the immunomodulatory properties of the phytogenic tested against a bacterial infection, an in vivo challenge with Aeromonas salmonicida was performed. A total number of 1,027 differentially expressed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 109 publications
(140 reference statements)
2
10
0
1
Order By: Relevance
“…In our study, we observed a modulation of the biological process "Regulation of I-kappaB kinase/NF-kappaB signaling (GO:0043122)". This modulation is in line with a recent study from our group, in which we demonstrated that a phytogenic feed additive from the olive fruit (Olea europaea), with biochemical and functional properties similar to MPLE, was also able to modulate biological process such as "Regulation of I-kappaB kinase/NF-kappaB signaling" (Salomón et al, 2021b).…”
Section: Interferon Gamma Mediated Signaling Pathway and Autophagysupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, we observed a modulation of the biological process "Regulation of I-kappaB kinase/NF-kappaB signaling (GO:0043122)". This modulation is in line with a recent study from our group, in which we demonstrated that a phytogenic feed additive from the olive fruit (Olea europaea), with biochemical and functional properties similar to MPLE, was also able to modulate biological process such as "Regulation of I-kappaB kinase/NF-kappaB signaling" (Salomón et al, 2021b).…”
Section: Interferon Gamma Mediated Signaling Pathway and Autophagysupporting
confidence: 90%
“…In this context, eight of the ten hub genes related to leukocyte activation (fn1, notch1, grb2, rac2, rdx, ezr, smad3, abl1) were upregulated. Similarly, a modulation of immunerelated GOs such as "Leukocyte activation involved in immune response" were enriched in Atlantic salmon smolts fed a feed additive AQUOLIVE R as we mentioned above from a phytogenic derived from olive (O. europaea) fruit with similar biochemical and functional properties to the MPLE phytogenic tested in the current study (Salomón et al, 2021b). For instance, notch1 a gene we have previously discussed highlighting its connection between NF-κB and IFN-γ as biological processes that have a key role in the differentiation of granulocytes, macrophages, and dendritic cells (Schroeder et al, 2003;Monsalve et al, 2009).…”
Section: Leukocyte Activation Involved In Immune and B Cells Signalin...mentioning
confidence: 73%
See 3 more Smart Citations